Assessing South Africa’s Potential to Address Climate Change Impacts and Adaptation in the Fisheries Sector - Ortega-Cisneros, Kelly; Cochrane, Kevern L.; Rivers, Nina; Sauer, Warwick H. H. (Frontiers in Marine Science, 2021)
The marine fisheries sector is one of the most important income sectors in South Africa and plays an important role in food security for small-scale and subsistence fishers. Climate-driven impacts have resulted in distribution shifts and declines in abundance of important fisheries targets, with negative consequences to the users dependent on these resources. The sustainability of the sector depends on its readiness to adapt to climate change. The inclusion of climate change impacts and adaptation in fisheries management documents in South Africa is essential to ensure adequate climate adaptation responses are implemented at the short- and long-term. This study aims to 1) determine if the relevant fisheries national management documents address climate change and adaptation, 2) determine if the relevant national climate change documents address climate change and adaptation in the fisheries sector and 3) evaluate the extent to which fisheries management documents address climate change and adaptation. A content analysis of fisheries management and climate change documents was carried out to determine if they incorporated information on climate change impacts and adaptation and marine fisheries respectively. Fisheries management documents were then screened against nine pre-determined criteria (or themes) based on climate change adaptation to determine the level of inclusion of best practice for climate change adaptation. Results indicate that climate change impacts and adaptation are rarely incorporated in the main fisheries management documents, except for the Climate Change Adaptation and Mitigation Plan for the agriculture, fisheries and forestry sectors. However, this document is still waiting to be adopted. The only direct reference identified in all the fisheries documents that supports climate change adaptation was ‘conservation and sustainable management of biodiversity’. With regards to indirect references to climate change adaptation, ‘equity’, ‘participatory management’ and ‘capacity building’ were most frequently incorporated in fisheries management documents. There is a need to explicitly incorporate information on climate change impacts and adaptation in South African fisheries management documents and increase the human and financial capacity at national institutions to ensure that the fisheries sector can adequately adapt to climate change.